Interactions between calcium release pathways: multiple messengers and multiple stores. - Galione, A; Churchill, G (2002)
The discovery of cyclic adenosine diphosphate ribose (cADPR) and nicotinic acid adenine dinucleotide phosphate (NAADP) as Ca(2+) releasing messengers has provided additional insight into how complex Ca(2+) signalling patterns are generated. There is mounting evidence that these molecules along with the more established messenger, myo-inositol 1,4,5-trisphosphate (IP(3)), have a widespread messenger role in shaping Ca(2+) signals in many cell types. These molecules have distinct structures and act on specific Ca(2+) release mechanisms. Emerging principles are that cADPR enhances the Ca(2+) sensitivity of ryanodine receptors (RYRs) to produce prolonged Ca(2+) signals through Ca(2+)-induced Ca(2+) release (CICR), while NAADP acts on a novel Ca(2+) release mechanism to produce a local trigger Ca(2+) signal which can be amplified by CICR by recruiting other Ca(2+) release mechanisms. Whilst IP(3) and cADPR mobilise Ca(2+) from the endoplasmic reticulum (ER), recent evidence from the sea urchin egg suggests that the major NAADP-sensitive Ca(2+) stores are reserve granules, acidic lysosomal-related organelles. In this review we summarise the role of multiple Ca(2+) mobilising messengers, Ca(2+) release channels and Ca(2+) stores, and the interplay between them, in the generation of specific Ca(2+) signals. Focusing upon cADPR and NAADP, we discuss how cellular stimuli may draw upon different combinations of these messengers to produce distinct Ca(2+) signalling signatures.